2011
DOI: 10.1111/j.1468-3083.2011.04148.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of anticellulite treatment using tripolar radiofrequency monitored by classic and high‐frequency ultrasound

Abstract: Radiofrequency enables cellulite reduction. A crucial aspect is proper monitoring of the progress of such therapy, which ultrasound allows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 21 publications
2
21
0
16
Order By: Relevance
“…Not all studies contained information on how long the tempera- to the intensities used, but these vary with the patient's feedback and with the equipment used. 3,4,15,16,18,[20][21][22] As for the total number of sessions, they ranged from 1 to 36, this being an estimate (article refers to home application 2-3 times a week for 3 months). As for the interval between sessions, two articles refer to a 2-week interval and eight articles refer to a 1-week interval.…”
Section: Resultsmentioning
confidence: 99%
“…Not all studies contained information on how long the tempera- to the intensities used, but these vary with the patient's feedback and with the equipment used. 3,4,15,16,18,[20][21][22] As for the total number of sessions, they ranged from 1 to 36, this being an estimate (article refers to home application 2-3 times a week for 3 months). As for the interval between sessions, two articles refer to a 2-week interval and eight articles refer to a 1-week interval.…”
Section: Resultsmentioning
confidence: 99%
“…Subcutaneous tissue thickness is a more simple parameter that may be assessed by classical US and has shown correlation with the grade of cellulite [46] and its decrease occurred together with clinical improvement in other studies [52,53]. We believe that those parameters may be useful in future cellulite studies but should not be used alone.…”
Section: Psoriasismentioning
confidence: 94%
“…Besides, other studies have found no correlation between dermis thickness and cellulite severity [46] or cellulite improvement [49]. Even so, some treatments have been suggested to be affective based on skin thickness reduction and increased echogenicity [51,52], but without significant correlation between patients satisfaction grade or clinical evaluation in one of them [51]. Regarding dermal echogenicity, a study has detected a grade effect with a marked decreased echogenicity of the superficial and deep dermis in more severe cellulite skin especially from the age of 30 [46].…”
Section: Cellulitementioning
confidence: 98%
See 1 more Smart Citation
“…1064 nm Nd:YAG laser appear to improve mild to moderate cellulite also [23]. Radiofrequency is able to reduce cellulite in a randomized trial [24]. A combination of radial ESWT and cryolipolysis has been included in this metanalysis showing a substantial fat thickness reduction of 3 cm and a circumference reduction by 4.5 cm in a cohort trial from Italy [25].…”
Section: Combination Therapymentioning
confidence: 96%